Quadratic energy–momentum squared gravity: Constraints from big bang nucleosynthesis - Akarsu, Özgür; Bouhmadi-López, Mariam; Katırcı, Nihan; Uzun, N. Merve (Elsevier BV, 2024)
In this study, we extend the standard cosmological model within the quadratic energy-momentum squared gravity (qEMSG) framework, introducing a nonminimal interaction between the usual material field ($T_{μν}$) and its accompanying quadratic energy-momentum squared field (qEMSF, $T_{μν}^{\rm qEMSF}$), defined by $f(\mathbf{T}^2) = α\mathbf{T}^2$ with $\mathbf{T^2}=T_{μν}T^{μν}$. Focusing on high energy scales relevant to big bang nucleosynthesis (BBN), we employ $^4$He abundance to constrain the parameter $α$. Our analysis selects the radiation-dominated universe solution compatible with the standard cosmological model limit as $α\rightarrow 0$ and reveals that qEMSF interaction model can modify the radiation energy density's evolution, potentially altering neutron-proton interconversion rates and consequently affecting $^4$He abundance in various ways. We establish the most stringent cosmological bounds on $α$: $(-8.81 \leq α\leq 8.14) \times 10^{-27} \, \mathrm{eV}^{-4}$ (68\% CL) from Aver \textit{et al.}'s primordial $^4$He abundance measurements, aligning with $α=0$. Additionally, $(3.48 \leqα\leq 4.43)\,\times 10^{-27} \rm{eV}^{-4}$ (68\% CL) from Fields \textit{et al.}'s estimates, utilizing the Planck-CMB estimated baryon density within the standard cosmological model framework, diverges from $α=0$, thereby lending support to the qEMSF interaction model. The study also highlights the bidirectional nature of energy-momentum/entropy transfer in qEMSF interaction model, depending on the sign of $α$. The implications of qEMSF in the presence of additional relativistic relics are also explored, showcasing the model's potential to accommodate deviations from standard cosmology and the Standard Model of particle physics.

14 pages, 2 figures
Keywords: Cosmology and Nongalactic Astrophysics (astro-ph.CO); FOS: Physical sciences; General Relativity and Quantum Cosmology (gr-qc); General Relativity and Quantum Cosmology; Astrophysics - Cosmology and Nongalactic Astrophysics